Motivation of Millennials in the Small and Medium-Sized Family Enterprises in Shaoxing, China - DAI, JIE (2016)
This research investigates how managers motivate millennial employees in Chinese family-owned small and medium-sized enterprises (SMEs), so it aims to find the current motivation methods in Chinese family-owned SMEs. In particular, This research more focuses on Shaoxing family-owned SMEs. The semi-structured interview is used to collect data in this research.